Assessment of oral health attitude & behaviour among dental student of Bhopal Madhya Pradesh: a comparative study - Agrawal, Riya (International Journal of Dental Research, 2017)
Introduction: Attitudes & behavior towards their own oral health affect their oral health habits and also have a possible influence for the improvement of the oral health of their patients and society.Aim: To evaluate oral health attitude & behavior among a group of dental students of one of the dental colleges of M.P. & to compare a difference in oral health.Material & Method: A descriptive cross study was carried out between 200 dental students of people dental academy Bhopal M.P. India. Subjects were divided into 2 groups, i.e. group 1 pre-clinical group (first & second year) group 2 clinical group (third & fourth year). A self-administered questionnaire consisting of 13 questions on attitudes and practice towards oral health care.Results: In the present study, 130 students were from preclinical group, and 70 students were from clinical group. Most of the students brush their teeth once daily for 2 min following roll technique of brushing before breakfast using only toothpaste as a cleaning aid. All students from clinical years routinely examined their oral cavity while most of the students visited the dentist only when required. Majority of students considered oral health as important as general health and believed that oral health affects the general health. Students were also aware of the harmful effects of tobacco while only few of them were indulged in them.Conclusion: With increasing years of the study, some aspects of dental student's oral health attitude and behavior improved but this improvement was limited. Thus, the students should be motivated to become an example of oral health in the society, for which few steps to motivate them toward better oral health are proposed.